The earnings of American Jewish men: human capital, denomination and religiosity - Barry R. Chiswick; Jidong Huang (Institute for the Study of Labor (IZA), 2006)
This paper analyzes the determinants of the earnings of American Jewish men using the 2000/01 National Jewish Population Survey. Non-response to the question on earnings is analyzed. Earnings are related to conventional human capital variables, as well as Jewish-specific variables. Except for the size of place and region variables, the standard human capital variables have similar effects for Jews and the general population. Jewish day schooling as a youth enhances earnings. Earnings vary by denomination, with Conservative Jews earning the most. The effect on earnings of religiosity (measured by synagogue attendance) is not monotonic. Earnings are highest for those who attend only once a week
Keywords: 330